ANALISIS MANNER DALAM DEBAT MERDEKA BELAJAR OLEH MAHASISWA MAGISTER PENDIDIKAN BAHASA INDONESIA UNIVERSITAS MUHAMMADIYAH SURAKARTA - safitri zuliana aryanti; Atiqa Sabardila (Universitas Negeri Makassar, 2020)
This research is intended to 1) describe the types of linguistic aspects by way of debate. 2) describing the analysis of linguistic aspects in the free learning debate. The main discussion of this study is qualitative research based on descriptive data that contains the results of orthographic debate transcription. The data source of this research is from MPBI UMS students. The results of this study (1) the types of linguistic aspects of the way in the debate are the use of language styles, language variations, diction, complex sentences, and conjunctions. (2) based on the analysis results students understand the linguistic aspects so that in the independent debate students learn to use several linguistic aspects but there are linguistic aspects that are used that are not appropriate or inappropriate. The conclusions from this study present several aspects of language by means of student debates, the language aspects that must be considered are: the use of language styles, language variations, diction, complex sentences, and conjunctions. The style of language used by students in the debate is reiteration and hyperbole language style. The variations in language used are various journalistic types, business language categories, casual language variations, various familiar languages. Dictations used are popular words, absorption words, foreign words and common words. The complex sentences used are paratactic and hypotactic complexes. The conjunctions used are coordinative conjunctions, and subordinative conjunctions